New technologies of hypotensive drug delivery in glaucoma treatment - O. A. Kiseleva; A. M. Bessmertny; L. V. Yakubova (Российский офтальмологический журнал, 2018)
The paper reports on promising methods of drug delivery in glaucoma treatment: contact lenses, punctum plugs, intraocular implants, subconjunctival and supraciliary injections, ocular rings, hydrogels, nanocarriers.